A Novel PARP Inhibitor YHP-836 For the Treatment of BRCA-Deficiency Cancers - Du, Tingting; Zhang, Zhihui; Zhou, Jie; Sheng, Li; Yao, Haiping; Ji, Ming; Xu, Bailing; Chen, Xiaoguang (Frontiers in Pharmacology, 2022)
PARP inhibitors have clinically demonstrated good antitumor activity in patients with BRCA mutations. Here, we described YHP-836, a novel PARP inhibitor. YHP-836 demonstrated excellent inhibitory activity for both PARP1 and PARP2 enzymes. It also allosterically regulated PARP1 and PARP2 via DNA trapping. YHP-836 showed cytotoxicity in tumor cell lines with BRCA mutations and induced cell cycle arrest in G2/M phase. YHP-836 also sensitized tumor cells to chemotherapy agents in vitro. Oral administration of YHP-836 elicited remarkable antitumor activity either as a single-agent or in combination with chemotherapy agents in vivo. These results indicated that YHP-836 is a well-defined PARP inhibitor.